2021
DOI: 10.3389/fphar.2021.754241
|View full text |Cite
|
Sign up to set email alerts
|

Phillyrin for COVID-19 and Influenza Co-infection: A Potential Therapeutic Strategy Targeting Host Based on Bioinformatics Analysis

Abstract: Background: The risk of co-epidemic between COVID-19 and influenza is very high, so it is urgent to find a treatment strategy for the co-infection. Previous studies have shown that phillyrin can not only inhibit the replication of the two viruses, but also has a good anti-inflammatory effect, which is expected to become a candidate compound against COVID-19 and influenza.Objective: To explore the possibility of phillyrin as a candidate compound for the treatment of COVID-19 and influenza co-infection and to sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 46 publications
(45 reference statements)
0
14
0
Order By: Relevance
“…76 Although there is no clear consensus on the implications of coinfection, one study suggests there is a potential for added harm with viral coinfection, because posttranslational changes in angiotensin-converting enzyme-2 by influenza A may increase vulnerability to lung injury and acute respiratory distress syndrome (ARDS) during coinfections. 77 Although potential targets for therapy are under investigation, 78 no single medication is known to treat both SARS-CoV-2 and influenza simultaneously, although supportive care can be given for both. Similar to influenza infections, as many as one-fifth of patients with SARS-CoV-2 are found to have coinfection or superinfection with other pathogens, which increases mortality, and these coinfections and superinfections are discussed further in this article.…”
Section: Severe Acute Respiratory Syndrome Coronavirus 2 and Viral Co...mentioning
confidence: 99%
“…76 Although there is no clear consensus on the implications of coinfection, one study suggests there is a potential for added harm with viral coinfection, because posttranslational changes in angiotensin-converting enzyme-2 by influenza A may increase vulnerability to lung injury and acute respiratory distress syndrome (ARDS) during coinfections. 77 Although potential targets for therapy are under investigation, 78 no single medication is known to treat both SARS-CoV-2 and influenza simultaneously, although supportive care can be given for both. Similar to influenza infections, as many as one-fifth of patients with SARS-CoV-2 are found to have coinfection or superinfection with other pathogens, which increases mortality, and these coinfections and superinfections are discussed further in this article.…”
Section: Severe Acute Respiratory Syndrome Coronavirus 2 and Viral Co...mentioning
confidence: 99%
“… 387 Further, Lai et al discovered that phillyrin could be used to treat COVID-19 and influenza co-infection since it not only inhibits the replication of both viruses, but also possesses the ability to regulate hypoxia-cytokine storm based on bioinformatics network pharmacology analysis. 388 …”
Section: Structures Of Small Molecule Drugs For Covid-19 Therapymentioning
confidence: 99%
“…Bioinformatics analysis revealed that phillyrin interacted with 192 common core targets and 25 biological pathways to treat the co‐infection of SARS‐COV‐2 and influenza virus. It was suggested that the compound activates the PI3K‐AKT, RAS, and HIF‐1 signaling pathways to regulate the body's immune and antiinflammatory effects, thereby reducing the severity of diseases caused by SARS‐COV‐2 and influenza virus infections (Lai et al, 2021 ).…”
Section: Search For Natural Antiviral Agents Against Sars‐cov ...mentioning
confidence: 99%